PWE-058 Factors associated with inflammatory bowel disease associated colorectal cancer and damage associated mucosal lesiondetection. (8th June 2018) - Sivananthan, Arun; Appleby, Richard; Kaur, Dataar; Kawsar, Anusuya; Millar, Kate; Mills, Katie; Rimmer, Stephanie; Goldin, Rob; Hoare, Jonathan
Abstract : Introduction: Colonoscopic surveillance is indicated for the detection of premalignant damage associated mucosal lesion (DALMs) and colorectal cancer (CRC) in patients with chronic inflammatory colitis of greater than 10 years duration. We reviewed all cases of DALM and CRC detection in our IBD cohort over a 4 year period and compared against current BSG guidance for high risk groups (2010). Methods: The pathology reporting system of Imperial College Healthcare NHS Trust was interrogated for SNOMED 11a codes for IBD and dysplasia or CRC (D6214, D6216, D6255 and M7400) between 1/9/12–1/1/17. The case notes of these patients were reviewed and those with adenoma related dysplasia excluded. The indication for the detecting procedure was recorded. Surveillance practice during this time was measured by recording all colonoscopies performed for the indication of IBD (colitis, Crohns disease, colitis – ulcerative or IBD assessment) over a 9 year period (1/9/07–1/1/17) from the endoscopy reporting system (Scorpio, Emis Health, UK) of Imperial College Healthcare NHS Trust. The surveillance interval of each individual patient was calculated. A subgroup of 20 patients within this cohort were sampled for case notes review to identify the reasons for inappropriate surveillance. Results: Dysplasia and IBD was detected in 59 individuals, 42 were adenomas and excluded, leaving 7 DALMs detected. Three (42%) were not detected during surveillance (two<10 years from symptom onset, one bowel cancer screening program). Two (29%) had cancer. Four (58%) were recognised as DALMs under white light endoscopy, three (42%) were detected on random biopsy, none were detected with dyespray. Adherence to the 2010 guidelines in these patients was 85%. 1289 individuals with 2256 colonoscopies were identified. Low/moderate/high risk groups were 78 (60%)/382 (29%)/125 (9.7%) respectively. Interval adherence in this cohort was 82%. 20 patients were selected for case notes review. The mean age was 52 (range 31–72). Three patients had colectomy (2 refractory colitis, one DALM) and one patient moved out of area during the studied period. 72 colonoscopies were performed with 52 intervals recorded. Seven (13%) intervals were scheduled over the recommended time (mean 333 days). These were all at the patient's request. 30 intervals (58%) were performed before there intended date (mean −347 days). The most common reason for this was inappropriate yearly surveillance. Conclusions: DALMs were detected in 0.5% of IBD patients undergoing colonoscopy. Almost half of these were not detected during scheduled surveillance, which may support the shorter intervals used by some clinicians.